Ionic Liquids and Organic Ionic Plastic Crystals: Advanced Electrolytes for Safer High Performance Sodium Energy Storage Technologies. Issue 17 (2nd May 2018) - Basile, Andrew; Hilder, Matthias; Makhlooghiazad, Faezeh; Pozo‐Gonzalo, Cristina; MacFarlane, Douglas R.; Howlett, Patrick C.; Forsyth, Maria
Abstract: Electrolytes composed entirely of salts, namely, ionic liquid solvents paired with a target ion salt, have been studied extensively within lithium batteries and have recently garnered interest as advanced electrolytes for sodium chemistries. In this review, the unique properties of ionic liquid electrolytes and their solid‐state analogs, organic ionic plastic crystals, are examined. Structure–property relationships, the effect of salt addition, cation and anion functionalization, and their effect upon physicochemical and thermal character are discussed. The authors discuss the use of ionic liquid electrolytes paired with organic solvents (referred to as hybrids) and briefly present the impact of using water as an additive. The majority of the literature presented herein covers studies of sodium electrolytes at Na + concentrations greater than 50 mol%, labelled as superconcentrated electrolytes, which have recently been investigated for their beneficial device performance and improved target ion mobility. The developing research of ionic liquids toward the oxygen reduction reaction is also presented toward the realization of Na–O2 chemistries to rival that of conventional Li‐ion; gaining fundamental understanding of the active species during discharge, its resultant nucleation and character. Additionally, the properties of the electrode–electrolyte interface resulting from the interaction between typical sodium anodes with ionic liquid electrolytes are discussed. Abstract : Ionic liquids are promising sodium battery electrolytes due to many of their favorable properties. Recent reports have described interesting cell performance dependent upon temperature, salt form, or concentration as well as the cation/anion functionality. These can be tailored through the flexibility of ion choice when designing ionic liquid or organic ionic plastic crystals electrolytes, to suit sodium energy storage.